A Complement to the Fredholm Theory of Elliptic Systems on Bounded Domains. (14th July 2009) - Rabier, Patrick J.
Abstract : We fill a gap in theL p theory of elliptic systems on bounded domains, by proving thep -independence of the index and null-space under "minimal" smoothness assumptions. This result has been known for long if additional regularity is assumed and in various other special cases, possibly for a limited range of values ofp . Here, p -independence is proved in full generality.